Reliability and Validity of the Geriatric Depression Scale in a Sample of Portuguese Older Adults with Mild-to-Moderate Cognitive Impairment - Apóstolo, João Luís Alves (2023)
Abstract Although the Geriatric Depression Scale (GDS) is a well-established instrument for the assessment of depressive symptoms in older adults, this has not been validated specifically for Portuguese older adults with cognitive impairment. The objective of this study was to analyze the psychometric properties of two Portuguese versions of the GDS (GDS-27 and GDS-15) in a sample of Portuguese older adults with mild-to-moderate cognitive impairment. Clinicians assessed for major depressive disorder and cognitive functioning in 117 participants with mild-to-moderate cognitive decline (76.9% female, Mage = 83.66 years). The internal consistency of GDS-27 and GDS-15 were 0.874 and 0.812, respectively. There was a significant correlation between GDS-27 and GDS-15 with the Beck Depression Inventory-II (GDS-27: rho = 0.738, p < 0.001; GDS-15: rho = 0.760, p < 0.001), suggesting good validity. A cutoff point of 15/16 in GDS-27 and 8/9 in GDS-15 resulted in the identification of persons with depression (GDS-27: sensitivity 100%, specificity 63%; GDS-15: sensitivity 90%, specificity 62%). Overall, the GDS-27 and GDS-15 are reliable and valid instruments for the assessment of depression in Portuguese-speaking older adults with cognitive impairment.